4m+2m(m=9)

Simple and best practice solution for 4m+2m(m=9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4m+2m(m=9) equation:



4m+2m(m=9)
We move all terms to the left:
4m+2m(m-(9))=0
We multiply parentheses
2m^2+4m-18m=0
We add all the numbers together, and all the variables
2m^2-14m=0
a = 2; b = -14; c = 0;
Δ = b2-4ac
Δ = -142-4·2·0
Δ = 196
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{196}=14$
$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-14)-14}{2*2}=\frac{0}{4} =0 $
$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-14)+14}{2*2}=\frac{28}{4} =7 $

See similar equations:

| x/2-12=32 | | 42/t=14 | | -7-19p=-8-19p+1 | | 113=5u+13 | | .47^2x=1/4 | | (x+20)3=5x | | -16-15z=-17z+18-15z | | -2u+5.52=4.22 | | 9u-9u=24 | | 16+7v-12=7v+4 | | Y=63x+825 | | x/49=30/35 | | 10-10h=10+12-10h | | 3x−7= 7x+13 | | 3+3v=12.9 | | −6=x5 | | Y+3+15+12=x-3 | | 3(x)+x+2(x)-1=251 | | -12=4f+8 | | 5y(y+2/5)=-13 | | 150-x-2x=120+2xX= | | 3y+4=2y+3 | | 6x−8=  8x | | 10w+2=10w+2=  8282 | | 60+0.10x=75+0.03x | | -19+10t=-6+10t-13 | | 0.05x0.5=0.025 | | 5(y+2}{5}25)=-13 | | w/5+11=18 | | 4d-4=5d−8 | | -41+x/5=-6 | | 8(8a+7)=-8(-7-8a) |

Equations solver categories